2020
DOI: 10.1080/17405904.2019.1708763
|View full text |Cite
|
Sign up to set email alerts
|

The discourse of the US alt-right online – a case study of the Traditionalist Worker Party blog

Abstract: The use of social media by extreme right groups and the selfproclaimed formation of the 'alt-right' in recent years have been linked to the rise in US white nationalism. Against a backdrop of widespread concern regarding the growing nature of the 'altright' phenomenon, this article responds to the pressing need to understand its appeal. Specifically, we examine the discursive means by which a hitherto unexamined US 'alt-right' group, the Traditionalist Worker Party, constructs its group identity and ideology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…The US has a particularly large and active right-wing digital news infrastructure, which has been associated with increasing distrust in traditional news media [114,115]. Within this broader architecture, the Alt-Right has an expansive online media environment encompassing a variety of platforms and content creators, including dedicated Alt-Right news sites, blogs, podcasts, YouTube videos, memes, and social media [115][116][117][118][119][120][121]. Furthermore, Alt-Right adjacent communities on YouTube, the Alt-Light, and Intellectual Dark Web, have served as entry points to the more extremist content of the movement [120,122].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The US has a particularly large and active right-wing digital news infrastructure, which has been associated with increasing distrust in traditional news media [114,115]. Within this broader architecture, the Alt-Right has an expansive online media environment encompassing a variety of platforms and content creators, including dedicated Alt-Right news sites, blogs, podcasts, YouTube videos, memes, and social media [115][116][117][118][119][120][121]. Furthermore, Alt-Right adjacent communities on YouTube, the Alt-Light, and Intellectual Dark Web, have served as entry points to the more extremist content of the movement [120,122].…”
Section: Discussionmentioning
confidence: 99%
“…These sources are further amplified through social media, allowing the movement to continue to grow and maintain visibility. Narratives on joining the Alt-Right most often reference this media environment rather than traditional conservative news [116,118,120,123]. Furthermore, research on the Alt-Right in Europe found that members are often distrustful of traditional media and rely on social media as their primary news source [123].…”
Section: Discussionmentioning
confidence: 99%
“…We merge this traditional multimodal discourse analysis with literature around alt-right discourses. In a recent study, Lorenzo-Dus and Nouri (2021) highlight five recurrent discourses among the alt-right, including groupness, political politics, race, religion, tradition, and change. Similarly, our research team examined the dataset to independently determine three to five discourses.…”
Section: Digital Multimodal Walkthrough Methods and Multimodal Discou...mentioning
confidence: 99%
“…186 As Lorenzo-Dus and Nouri explain, they then use these 'insults' (accusations of extremism) to 'lend further weight to their victimised group claims'. 187 As the powerlessness of the victim is pushed in one direction, the scale and power of the elite's ability to orchestrate events is forced the opposite way. To achieve a contrast, anti-woke actors need to construct the woke as powerful, unaccountable, cunning and beyond public scrutiny.…”
Section: Repudiating the Far Rightmentioning
confidence: 99%